Crosslinked HIV-1 envelope–CD4 receptor complexes elicit broadly cross-reactive neutralizing antibodies in rhesus macaques - Fouts, Timothy (The National Academy of Sciences, 2002)
The identification of HIV envelope structures that generate broadly cross-reactive neutralizing antibodies is a major goal for HIV-vaccine development. In this study, we evaluated one such structure, expressed as either a gp120–CD4 or a gp140–CD4 complex, for its ability to elicit a neutralizing antibody response. In rhesus macaques, covalently crosslinked complexes of soluble human CD4 (shCD4) and HIV-1(IIIB) envelope glycoproteins (gp120 or gp140) generated antibodies that neutralized a wide range of primary HIV-1 isolates regardless of the coreceptor usage or genetic subtype. Ig with cross-reactive neutralizing activity was recovered by affinity chromatography with a chimeric single-chain polypeptide containing sequences for HIV(BaL) gp120 and a mimetic peptide that induces a CD4-triggered envelope structure. These results suggest that covalently crosslinked complexes of the HIV-1 surface envelope glycoprotein and CD4 elicit broadly neutralizing humoral responses that, in part, may be directed against a novel epitope(s) found on the HIV-1 envelope.